Germination and biochemical changes in West Indian gherkin seeds under water stress at different temperatures - Almeida, João Paulo; Paiva, Emanoela; Torres, Salvador; Sá, Francisco Vanies; Leite, Moadir (Revista Ciência Agronômica, 2019)
Information on the effects of climate conditions on the survival of species grown in semi-arid regions is essential and at the same time scarce, especially regarding rustic species such as West Indian gherkin (Cucumis anguria L.). Thus, this study aimed to evaluate germination, growth and biochemical alterations in C. anguria seeds under water stress and different temperature regimes. The experimental design was completely randomized, in 5 x 5 factorial scheme, composed of five osmotic potentials (0.0; -0.1; -0.2; -0.3 and -0.4 MPa) and four temperatures (20; 25; 30 °C and alternating temperatures of 20-30 ºC), with each treatment composed of four replicates of 50 seeds. The seeds were sown on paper towel (Germitest®) and germinated in Biochemical Oxygen Demand (B.O.D.) germinators, under 8-h photoperiod. Germination percentage, germination speed index, mean time of germination, seedling length and contents of chlorophylls, carotenoids, proline, free amino acids and free sugars were determined along the experiment. Decrease in osmotic potential reduced germination, growth and contents of chloroplast pigments of C. anguria seedlings, but was more drastic at levels lower than -0.2 MPa. Low temperatures intensify the effects of water stress on the germination of C. anguria seeds. The synthesis of protecting osmolytes increased in C. anguria seedlings but these components did not promote efficient osmotic adjustment in their initial development stage.